The Influence of the Use of Electronic Medical Record Systems on Effective Doctor-Patient Communication Relationships in the Outpatient Clinic - Lestari, Nadia Putri; Ramadhani, Isniani; NurCita, Boenga; Kristanti, Melly (Universitas Muhammadiyah Yogyakarta, 2024)
Electronic medical records are being used based on the Regulation of the Minister of Health (PMK) number 24 of 2022 concerning Medical Records, which is a transition of patient medical records from conventional systems to electronic-based. This study aims to determine the effect of using an electronic medical record system on effective doctor-patient communication relationships in hospital outpatient clinics. This study was conducted at a B-class general hospital in Jakarta Regional General Hospital, using an analytical descriptive method and a cross-sectional approach. A total of 153 respondents followed quota sampling rules. The test used was the chi-square test, with the p-value being less than 0.05. Approximately 50% of respondents demonstrated high levels of effective doctor-patient communication and high levels of knowledge on the use of RME. This study states that there is a positive relationship between the use of electronic medical records and effective communication between doctors and patients.